UJI TOKSISITAS AKUT EKSTRAK PROPOLIS LEBAH KELULUT Geniotrigona thoracica DAN Heterotrigona itama TERHADAP MENCIT (Mus musculus L.) - Nindya Ila Syafira Ramelan; Paula Mariana Kustiawan (Sekolah Tinggi Ilmu Kesehatan Samarinda, 2024)
Propolis is a product produced by bees that has various benefits. As a natural substance that can be used for medicinal purposes, propolis needs to undergo acute toxicity testing to determine the safety of its use and to estimate the degree of damage that may occur. This study aims to compare the acute toxicity potential of propolis extracts from two species of stingless bees, Geniotrigona thoracica and Heterotrigona itama, based on LD50 and to assess toxic symptoms. The testing was conducted using the Organization for Economic Co-operation and Development (OECD) No. 425 method: Acute Oral Toxicity (UDP). Phytochemical test results showed that propolis extracts from Geniotrigona thoracica and Heterotrigona itama have consistent levels of secondary metabolites, namely flavonoids, alkaloids, tanins, and phenolics. Based on the acute toxicity test results, it can be concluded that the propolis extracts from Geniotrigona thoracica and Heterotrigona itama have consistent LD50 values, exceeding 5000 mg/kg body weight, and are classified as non-toxic.